Implementation of Sea Work Agreement for Work Safety Insurance Program for Fishing Vessel Crew - Julianto Jover Jotam Kalalo; Restu Monika Nia Betaubun; Rudini Hasyim Rado; Rulfino Rupang (JILPR Journal Indonesia Law and Policy Review, 2023)
Sea Work Agreement is a written agreement between the crew of the Fishing Vessel and the owner of the Fishing Vessel or the operator of the Fishing Vessel or the skipper or agent of the crew of the Fishing Vessel which is a provision in Article 1 number 65 of Government Regulation (PP) Number 27 of 2021. The purpose of this study is to find out and understand the implementation of the sea work agreement as well as the forms of protection and settlement efforts in the event of a breach of the sea work agreement. The type of research carried out is Juridical Empirical Research, using the law approach and the case approach. In the results of this study, it is explained that the implementation of the sea work agreement is a work safety insurance program for fishing vessel crews which is an agreement that must be carried out by everyone who does work at sea. This sea work agreement is carried out between the two parties, namely between a shipping entrepreneur who owns a ship company as one party and a worker or ship crew on the other. In relation to the implementation of the sea work agreement, seen from the form, content and format, the flow of the implementation process up to the marine work agreement insurance program has been implemented based on the provisions of the applicable laws and regulations, although there are obstacles found and faced in the field. Then the form of protection provided is to ensure the fulfillment of the rights and obligations of the parties who carry out the Sea Work Agreement, namely to fishing vessel crews in the form of risk protection while working and to fishing companies in the form of business risk protection while working. As for the efforts made when the default occurs, namely the settlement of the parties by deliberation to reach an agreement. If an agreement is not reached, the dispute is resolved through mediation.